"The Horse on which Words Ride": Proverbial Narrative in Toyin Falola's A Mouth Sweeter than Salt - Felicia Ohwovoriole (Yoruba Studies Review)
Literature and oral tradition share a symbiotic relationship. Toyin Faiola the author of A Mouth Sweeter than Salt has produced a highly engaging memoir. The text is set in Ibadan, Ode Aje and Ilorin. We find a rich and knowledgeable exploitation of oral forms which the author uses within the frame of the biographical genre. Through the use of proverbial narration, FaIola presents a tale replete with magic, religion, divination, spirituality and various folklore elements. The oral forms Faiola has used in the text come from the oral character of everyday life, prose narratives, songs, proverbs and proverb-like expressions while exploring the themes of innocence, curiosity and growth. This stylistic feature of narration is common in African story telling sessions. In both the traditional and modern context, the African proverb fulfils its social and communicative function in various forms. Faiola presents an inseparable relationship of mutual exchange between the oral and written traditions. However, our point of emphasis is to evaluate the context and usage of the proverbial narration with a restriction to proverbs which deal with animals. The qualities attributed to animals in the proverbs and sayings figuratively and metaphorically describe people's appearance, characteristics and deeds.